1994
DOI: 10.1093/ageing/23.5.418
|View full text |Cite
|
Sign up to set email alerts
|

A General Population Survey of Rest Cramps

Abstract: Two hundred and eighteen subjects, out of 250 individuals taken from a general practice register, returned completed questionnaires giving details about rest cramps, and a further 15 were contacted by telephone. The overall prevalence of rest cramps in the survey population was 37%. The symptom was more prevalent in older subjects. Rest cramps were most commonly experienced in the muscles of the leg, in 83% of the 86 cramp sufferers. Symptoms were usually present at night (73%). On average cramp episodes laste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
96
2
2

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(112 citation statements)
references
References 0 publications
12
96
2
2
Order By: Relevance
“…Studies show that nocturnal leg cramps are frequent in elderly people and equally prevalent in men and women. Results suggest that there is co-morbidity between leg cramps and medical and neurological diseases, including periodic limb movement, diabetes and peripheral vascular disease (37)(38)(39). Nocturnal leg cramps are also associated with intake of alcohol, medications and blood levels of thyroid hormones, urea, creatinine, potassium, magnesium, calcium, and glucose (39).…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that nocturnal leg cramps are frequent in elderly people and equally prevalent in men and women. Results suggest that there is co-morbidity between leg cramps and medical and neurological diseases, including periodic limb movement, diabetes and peripheral vascular disease (37)(38)(39). Nocturnal leg cramps are also associated with intake of alcohol, medications and blood levels of thyroid hormones, urea, creatinine, potassium, magnesium, calcium, and glucose (39).…”
Section: Discussionmentioning
confidence: 99%
“…Participants who identified the particular movements that induced cramp described plantarflexion of the ankle joint as the trigger. 8 In the present study several patients (2,4,8,9, and 11) complained that they adopted an uncomfortable posture to avoid this movement for fear of calf cramps, and this physical strain may interrupt the initiation of sleep. Recent studies suggest that sleep fragmentation may be more critical to chronic pain than the quantity of sleep.…”
Section: Discussionmentioning
confidence: 69%
“…Five subjects had MTrP injection only once at T0 because they reported sufficient improvement of symptoms and they did not want additional treatment at T2. Five patients (2,4,8,9, and 11) reported that they were afraid to tense up their legs for fear of calf cramps.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…D uring th e tre a tm e n t period, participants were randomly assigned 300 mg daily dose of hydroquinine hydrobromide dihydrate (54 participants) or placebo (58). The frequency, severity (1)(2)(3)(4)(5)(6)(7)(8)(9)(10), duration, and location of muscle cramps, as well as any side-effects, were recorded by participants in daily diaries. The primary outcome measures were the number of muscle cramps and the number of days during which the participants had muscle cramps (cramp-days).…”
Section: Discussionmentioning
confidence: 99%